Pemberdayaan Masyarakat melalui Daur Ulang Sampah Plastik untuk Produksi Tikar di Gampong Rayeuk Paya Itek - Alhaddadi, Alhaddadi; Maqvirah, Annisa; Abrar, Faturrahman; Mastura, Fina; Rahmi, Intan Meutia; Nazila, Laini; Ayuna, Laiya; Mutmainnah, Mutmainnah; Ichsan, Muhammad; Safira, Nadia; Ramadhani, Ramadhani (Ibrah : Jurnal Pengabdian Kepada Masyarakat, 2024)
This research aims to empower the community of Gampong Rayeuk Paya Itek through the management of plastic waste into economic value products in the form of mats. The research objectives include improving community skills in recycling plastic waste, increasing awareness of the importance of waste management, and developing an online marketing network for craft products. The research used a participatory qualitative approach with the Participation action research (PAR) method through observation, training, and mentoring integrated in a 3R-based empowerment program (Reduce, Reuse, Recycle). Data was collected through interviews and documentation. The results showed the success of this program in environmental, social, and economic aspects. A total of 45 kg of plastic waste was successfully managed, creating a cleaner environment and increasing community awareness of the importance of recycling. Socially, the housewives' skills improved in processing plastic waste into mats, strengthening collaboration between residents, and creating positive synergy with student participation. The economic impact is in the form of additional income through the sale of mats for Rp25,000-Rp30,000 per piece, as well as wider market access through social media. The program also encourages sustainability through community commitment to continue production, continued training support from the village government, and community-based business development plans. The implications of the research include an effective community empowerment model in overcoming plastic waste problems, improving community welfare, and contributing to the literature on local empowerment-based plastic waste management.